2019
DOI: 10.1002/iub.2180
|View full text |Cite
|
Sign up to set email alerts
|

Cell transfer‐based immunotherapies in cancer: A review

Abstract: In cell transfer therapy (CTT), immune cells such as innate immune‐derived natural killer cells and dendritic cells as well as acquired immune‐related T lymphocytes such as tumor‐infiltrating lymphocytes and cytokine‐activated or genetically modified peripheral blood T cells are used in the management of cancer. These therapies are increasingly becoming the most used treatment modality in cancer after tumor resection, chemotherapy, and radiotherapy. In adoptive cell transfer, the lymphocytes isolated from eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 106 publications
(233 reference statements)
0
9
0
Order By: Relevance
“…One of the main advantages of this cell type is that they are found in high levels in blood under normal conditions, and in addition, their number can be incremented further upon in vivo treatment with G-CSF and GM-CSF cytokines ( 111 , 112 ). Another feature that makes them unique is that neutrophils do not need ex vivo culturing and expansion for a later infusion into the patient, compared to most other immune cells used therapeutically, such as T cells, NK cells or DCs ( 113 ). Siders et al showed that increasing the number of circulating neutrophils by a mere injection of G-CSF turned them into excellent cytotoxic cells that were able to kill alemtuzumab-opsonized cells in a xenograft model of a CD52 + tumor ( 114 ).…”
Section: Role Of Neutrophils In Tumor Eliminationmentioning
confidence: 99%
“…One of the main advantages of this cell type is that they are found in high levels in blood under normal conditions, and in addition, their number can be incremented further upon in vivo treatment with G-CSF and GM-CSF cytokines ( 111 , 112 ). Another feature that makes them unique is that neutrophils do not need ex vivo culturing and expansion for a later infusion into the patient, compared to most other immune cells used therapeutically, such as T cells, NK cells or DCs ( 113 ). Siders et al showed that increasing the number of circulating neutrophils by a mere injection of G-CSF turned them into excellent cytotoxic cells that were able to kill alemtuzumab-opsonized cells in a xenograft model of a CD52 + tumor ( 114 ).…”
Section: Role Of Neutrophils In Tumor Eliminationmentioning
confidence: 99%
“…Exciting achievements and outcomes were obtained in treating hematologic malignancies with CAR-T cells 4 , 5 , 8 and advanced or metastatic solid tumors with antibodies to cytotoxic T lymphocyte antigen-4 (CTLA-4 and programmed death-1 (PD-1)/programmed death-ligand 1 (PD-L1). 9 , 10 , 11 , 12 Additionally, adaptive cell therapy (ACT) has been widely accepted and applied in clinics with some promising results, 13 although it faces challenges of specificity and efficacy. 5 , 6 , 14 As such, researchers were looking for more specific immune cells for ACT.…”
Section: Introductionmentioning
confidence: 99%
“…Such modification has raised the acceptation levels of immune therapies. However, efficacy in delivering the antitumor immune response with immune stimulation is challenging, as it requires proper monitoring with minimum antigen loss and trafficking in a biological system [67]. Cancer vaccines are another form of cancer immunotherapies where tumor specific antigens (polypeptides, DNA and RNA) are exploited for building immunogenic response, which can trigger antitumor expressions, thereby, generating antitumor immunity with additional support from adjuvant molecules for improved tumor killing response.…”
Section: Cancer Immunotherapies Present Status and Concernsmentioning
confidence: 99%